2019
DOI: 10.1111/bjso.12318
|View full text |Cite
|
Sign up to set email alerts
|

Whose tweets? The rhetorical functions of social media use in developing the Black Lives Matter movement

Abstract: Research on collective action frequently characterizes social media as a tool for mobilization. However, social media activity can fulfil a variety of different functions for social change. In particular, the rhetorical functions of social media use by social movements are not well understood. We address this shortfall by analysing the rhetorical functions of Twitter use during an early stage of the Black Lives Matter social movement. We examine how activists used Twitter to balance competing aims for social c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 65 publications
1
28
0
1
Order By: Relevance
“…Making the distinction helps to test the hypothesis that allyship (in the sense of helping a group perceived to be distinct or different) may be more likely to arise from instrumental purposes (e.g., to achieve the ingroup's own political aims; Droogendyk, Wright, Lubensky, & Louis, 2016;Iyer & Ryan, 2009). Helping from a position of distance instead of solidarity would increase the likelihood of contested choices, such as selecting tactics without reference to disadvantaged groups' norms or misrepresenting their identity (Wilkins, Livingstone, & Levine, 2019). Allyship as opposed to solidarity would also increase dependency-affirming strategies that subtly keep disadvantaged group members "in their place" (Wiley & Dunne, 2019).…”
Section: Changes In Orientation To Other Groups Change Tacticsmentioning
confidence: 99%
“…Making the distinction helps to test the hypothesis that allyship (in the sense of helping a group perceived to be distinct or different) may be more likely to arise from instrumental purposes (e.g., to achieve the ingroup's own political aims; Droogendyk, Wright, Lubensky, & Louis, 2016;Iyer & Ryan, 2009). Helping from a position of distance instead of solidarity would increase the likelihood of contested choices, such as selecting tactics without reference to disadvantaged groups' norms or misrepresenting their identity (Wilkins, Livingstone, & Levine, 2019). Allyship as opposed to solidarity would also increase dependency-affirming strategies that subtly keep disadvantaged group members "in their place" (Wiley & Dunne, 2019).…”
Section: Changes In Orientation To Other Groups Change Tacticsmentioning
confidence: 99%
“…More than ever, due to technological advances and the effects of an isolating pandemic, social media has become a tool for mobilization and quick dissemination of information (Wilkins et al 2019;Gonz alez-Padilla and Tortolero-Blanco 2020;Kudchadkar and Carroll 2020). As expressed by Yeung (2018) social media remains a relatively untapped source to mobilize policy action and social change.…”
Section: Editorialmentioning
confidence: 99%
“…Revolutionizing the way in which we communicate, social media has the capacity to change our beliefs and attitudes, whom we connect with, and how we engage with social justice and activism (Gonta et al 2017;Yeung 2018). Using the Black Lives Matter movement as an example, phrases that have been often misconstrued as inoffensive such as 'All Lives Matter' have been called out and corrected on social media platforms (Gallagher et al 2018;Wilkins et al 2019). A study aimed at evaluating the relationship between media exposure, age and attitude on homosexuality concluded that higher media exposure levels fostered more accepting attitudes (Gonta et al 2017).…”
Section: Editorialmentioning
confidence: 99%
“…Kimoyo Beads are both a way of celebrating Wakandan culture and innovation, and also a way of communicating and sharing their ideas, morals and beliefs. Kimoyo Beads, and the ways that they are used and depicted within the Black Panther mythos, are comparable to social media, and how individuals use it to portrays themselves and their identity, whilst also using it as a tool to inform and share ideas with others (Hogan, 2010;Wilkins et al, 2019).…”
Section: Kimoyo Beads the Djalia And The Egungunmentioning
confidence: 99%